2020
DOI: 10.1111/jphp.13364
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin ameliorates experimental autoimmune encephalomyelitis (EAE) via immunomodulatory, anti-apoptotic and antioxidative activity

Abstract: Objectives Multiple sclerosis is a common autoimmune inflammatory disease of the central nervous system. There are several underlying mechanisms for the pathogenesis of the disease, including inflammation, oligodendrocyte apoptosis and oxidative stress. Methods The mechanism of action of shikonin was investigated in the C57BL/6 experimental autoimmune encephalomyelitis (EAE) model of multiple sclerosis. Key findings The results revealed that EAE induction significantly increased the extent of demyelination in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In addition, shikonin could inhibit the increase of serum renal injury index (blood proteinuria, serum creatinine, and urea nitrogen) induced by CLP in rats, indicating that shikonin could prevent sepsis‐mediated AKI. Previous studies have shown that shikonin has good antiapoptotic, anti‐inflammatory, and antioxidant effects (Nasrollahzadeh Sabet et al, 2020; C. Yang et al, 2018). It has been reported that shikonin could significantly improve acute lung injury induced by sepsis in vitro and in vivo experiments, and the mechanism was to increase the expression of miRNA‐140‐5p, and then down‐regulate the expression of TLR4, thereby inhibit the downstream myeloid differentiation protein 88 and NF‐κB protein expression (Y. Y. Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, shikonin could inhibit the increase of serum renal injury index (blood proteinuria, serum creatinine, and urea nitrogen) induced by CLP in rats, indicating that shikonin could prevent sepsis‐mediated AKI. Previous studies have shown that shikonin has good antiapoptotic, anti‐inflammatory, and antioxidant effects (Nasrollahzadeh Sabet et al, 2020; C. Yang et al, 2018). It has been reported that shikonin could significantly improve acute lung injury induced by sepsis in vitro and in vivo experiments, and the mechanism was to increase the expression of miRNA‐140‐5p, and then down‐regulate the expression of TLR4, thereby inhibit the downstream myeloid differentiation protein 88 and NF‐κB protein expression (Y. Y. Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Shikonin is a kind of naphthoquinone compounds from the roots of shikonin, which has a variety of pharmacological activities (C. Guo et al, 2019). Studies have shown that shikonin possessed antioxidant, antitumor, anti‐inflammatory, antiapoptotic, antiviral, and other biological characteristics (C. Chen et al, 2017; C. Huang et al, 2013; Nasrollahzadeh Sabet et al, 2020; J. Yang et al, 2017). The study showed that shikonin could significantly prevent acute lung injury in septic rats through immune regulation and inhibition of inflammation, and its mechanism might be related to miRNA‐140‐5p/TLR4 axis (Y. Y. Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Based on its ability to induce apoptosis in tumor tissue, SK has been widely investigated in cancer treatment [ 27 30 ]. In recent years, the antiapoptotic effects of SK have been gradually discovered in lung injury [ 31 ], myocardial ischemic/reperfusion injury [ 32 ], osteoarthritis [ 33 ], and nervous system diseases [ 18 , 20 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the expression levels of TGF-β and Bcl2 and the activity of GPx1 were significantly increased after shikonin treatment. These results suggest that shikonin has good immunomodulatory and antioxidant effects in EAE and may contribute to the remission of EAE [ 186 ].…”
Section: Natural Compounds Against Oxidative Stress In Animal Models ...mentioning
confidence: 99%